Health information seeking among Mbararan adolescents: results from the Uganda Media and You survey - Ybarra, Michele L.; Emenyonu, Kane; Nansera, Denis; Kiwanuka, Julius; Bangsberg, David R. (Health education research, 2008)
To maximize scarce intervention dollars, pediatricians and other adolescent health professionals must position health promotion efforts in mediums that most effectively reach youth. This may be especially true in resource-limited settings where access to primary health care and medications are limited. To improve the efficiency and impact of disease prevention and health promotion efforts in resource-limited settings, we examine sources of health information cited by adolescents in Mbarara Uganda. Participants in the Uganda Media and You survey were students aged 12–18 (n 5 500) randomly identified in five secondary schools in Mbarara municipality, Uganda. Ninety-three percent of eligible and invited youth completed the cross-sectional, pencil and- paper survey. Four in five adolescents (81%) indicated they turned to parents, teachers, and other adults while around half read a book/went to the library (56%) or turned to siblings and friends (50%) for information about health and disease. More than one in three (38%) indicated that they used the computer and Internet to search for health information. Older versus younger respondents tended to rely upon siblings and friends for all types of health questions. On the other hand, younger versus older youth were significantly more likely to turn to parents, teachers, and other adults for their questions about sexual health. Adults may be an important component of effective disease prevention and health promotion campaigns. Multiple delivery methods may be especially effective for reaching older adolescents. Technology also may be an important health promotion tool in resource-limited settings